Malignant Meningioma: An International Multicentre Retrospective Study. Issue 3 (19th December 2018) - Champeaux, Charles; Jecko, Vincent; Houston, Deborah; Thorne, Lewis; Dunn, Laurence; Fersht, Naomi; Khan, Akbar Ali; Resche-Rigon, Matthieu
ABSTRACT: BACKGROUND: In contrast to benign meningiomas, malignant meningiomas (MM) are rare and associated with an unfavourable prognosis. Reports on MM concern fairly small cohorts, often comprising less than 30 cases. OBJECTIVE: To describe the outcome MM and identify factors that may influence survival. METHODS: Pathology reports and clinical data of 178 patients treated between 1989 and 2017 for a MM at 6 different international institutions were retrospectively reviewed. Seventy-six patients (42.7%) had a previous history of grade I or grade II meningioma. The patients underwent a total of 380 surgical resections and 72.5% received radiotherapy. Median follow-up was 4.5 yr. RESULTS: At data collection, 111 patients were deceased (63.4%) and only 23 patients (13.7%) were alive without any residual tumor on the most recent scan. Median overall survival was 2.9 yr, 95% confidence interval [CI; 2.4, 4.5]. Overall survival rates at 1, 5, and 10 yr, respectively, were: 77.7%, 95% CI [71.6, 84.3], 40%, 95% CI [32.7, 49], and 27.9%, 95% CI [20.9, 37.3]. In the multivariable analysis, age at MM surgery <65 yr (hazard ratio [HR] = 0.44, 95% CI [0.29, 0.67], P < .001), previous benign or atypical meningioma surgery (HR = 1.9, 95% CI [1.23, 2.92], P = .004), completeness of resection (HR = 0.51, 95% CI [0.34, 0.78], P = .002), and adjuvant radiotherapy (HR = 0.64, 95% CI [0.42, 0.98], P = .039) were established as independent prognostic factors for survival. CONCLUSION: This large series confirms the poor prognosis associated with MM, the treatment of which remains challenging. Patients under 65-yr-old with primary MM may live longer after complete resection and postoperative radiotherapy. Even with aggressive treatments, local control remains difficult to achieve.